CIVIL WAR FIELD ARTILLERY : PROMISE AND PERFORMANCE ON THE BATTLEFIELD - Hess, Earl J. (Louisiana State University Press, 2023)
The American Civil War saw the creation of the largest, most potent artillery force ever deployed in a conflict fought in the Western Hemisphere. Its size was about as large and powerful as any raised in prior European wars. Moreover, Union and Confederate artillery included the largest number of rifled pieces fielded in any conflict in the world up to that point. Amazingly, Earl Hess's "Civil War Field Artillery" is the first comprehensive general history of the artillery arm that supported infantry and cavalry in the conflict. Hess examines the major factors that affected artillerists and their work, including the hardware (cannons, carriages, limbers, caissons, tubes, and the fuses that exploded ordnance), the organization of artillery power (assembling batteries, battalions, regiments, Union artillery brigades, and Confederate artillery battalions), relationships between artillery officers and infantry/cavalry commanders, environmental factors on the battlefield, and many other influences on effectiveness as well. Hess's study offers numerous new interpretations of Civil War artillery based on deep and expansive research, especially in available statistical data. For example, in terms of organizing and managing the artillery arm, officers of the era and subsequent historians alike decried the early war practice of dispersing the guns and assigning them to infantry brigades or divisions where infantry officers completely commanded them. They also praised the concentration system most major field armies put into place during the latter half of the war. However, based on the evidence, Hess suggests that the dispersal system of the early part of the war did not inhibit the concentration of artillery power on the battlefield and that the concentration system of the latter half of the conflict failed to produce more concentration of guns. Another example relates to the effectiveness of fuses to explode long-range ordnance. Previous historians have praised those fuses, admitting they had initial problems early in the war, which each side fixed. Hess's research clearly shows that was not the case. Battery commanders continued to report bad fuses to the very end of the war. Cumulative data on what type of projectiles commanders fired in battle shows that they lessened their use of the new long-range exploding ordnance due to bad fuses while increasing their use of solid shot, the oldest artillery projectile in history. Hess's wide-ranging study argues that Civil War field artillery failed to live up to its promise, especially rifled pieces. As a general history, it also covers all aspects of the history of field artillery in the conflict, including the life of the artilleryman, the use of artillery horses, manpower replacement practices, the effect of widespread use of field fortifications on artillery performance, and the problems of resupplying batteries in the field. His comprehensive coverage and new interpretations bring the history of field artillery up to date and will contribute to a re-envisioning of the military history of the Civil War